Chapter Venere e Cupido di palazzo Pandolfini a Firenze: una scultura inedita di Chiarissimo Fancelli - Cardini, Agnese (Studi e saggi, 2020)
This paper aims to add another piece of knowledge for Chiarissimo Fancelli, one of the leading sculptors in the Florentine art scene of the first thirty years of the Seventeenth century. The artwork, credited to the sculptor from Settignano, is located in palazzo Pandolfini (Florence) and represents Venus and Cupid. Through the analysis of both its style and available bibliographical and historical sources, the marble group can now be included in the corpus of Fancelli's sculptures and dated to 1620-1625.